Optimalisasi Biomassa Alga Hijau Ulva sp. Sebagai Biosorben Logam Berat Cr(VI) - Novianti, Anisa Dea; Karang, I Wayan Gede Astawa; Putra, I Nyoman Giri (Journal of Marine and Aquatic Sciences; Vol 6 No 1 (2020)DO - 10.24843/jmas.2020.v06.i01.p15, 2020)
Heavy metals are dangerous pollutants because it can’t be degraded by organism or can’t accumulated in environment. Heavy metals can settles at the bottom of the waters. One of the dangerous heavy metals is Hexavalent Chromium or Cr(VI). Research on reducing heavy metal pollution is important, there are many methods that can be use to reduce heavy metal. Biosorption one of the methods which is effective and efficient for reducing heavy metal pollution because the biomaterials or biosorbent used is able to absorb metals. The purpose of this research was to determine the optimum conditions for green algae which is Ulva sp. to adsorb Cr(VI) metal ions. Utilization of algae Ulva sp. as a biosorbent can help to reduce ecological problems due to algae that can bloom and also it can minimize pollution of heavy metals Cr(VI). Based on the results of the research the optimum conditions for biosorption of Cr(VI) by Ulva sp. influenced by several parameters such as pH, biosorbent dosem initial Cr(VI) concentration and contact time.   In this research the most optimal conditions for the biosorpstion of Cr(VI) using Ulva sp. as a biosorbent is at pH 2, the mass of biosorbent 10 gr, initial concentration of Cr(VI) 4 mg/L for 90 minutes. The maximum efficiencies of Cr(VI) removal was 98,88% and capacity for absorb was  0,093 mg/g.